Demographic Transition in the Middle East : Implications for Growth, Employment, and Housing - Bhattacharya, Rina (IMF Working Papers; Working Paper ;, 2000)
The working age population is expected to grow faster in the Middle East than in any other region in the world between now and 2015-rising annually by 2.7 percent, or 10 million people. This demographic explosion presents the region with a major challenge in terms of providing jobs, incomes, and housing for the growing population, but the expanding labor force can also be seen as an opportunity to generate higher per capita income growth on a sustainable basis. The paper concludes by emphasizing the importance of market-friendly institutions in turning the challenge into opportunity.